Sublingual allergen immunotherapy for respiratory allergies: what is new?. (December 2014) - Makatsori, Melina; Calderon, Moises A
<x xml:space="preserve">Abstract</x> Sublingual immunotherapy (SLIT) is a disease-modifying treatment for respiratory allergies that has been used for many years in Europe and has also recently been approved for use in North America. Its use is thus likely to increase. There is more evidence available regarding SLIT efficacy and its good safety profile, making it an appealing treatment option. The majority of studies have mostly focused on grass pollens; however, there are now data available regarding efficacy for other allergens. This review will summarize recent findings from SLIT clinical trials for respiratory allergies, including efficacy, safety, post-discontinuation effects and use in different age groups. Grass pollen, tree pollen, house dust mite and ragweed SLIT studies will be evaluated.